Características agronômicas e fisiológicas de plantas enxertadas e não enxertadas de mini melancia - Aumonde, Tiago Zanatta (2010)
The work was carried in the field between 2008 and 2009 at the Federal University of Pelotas and aimed to evaluate the mini watermelon cultivar Smile ® grafted and ungrafted. In the seedling stage were evalueted the survival rates and lignification. The rootstocks that provided the best results were transplanted to the field with ungrafted plants and where analyzed the growth, dry matter partitioning, production and fruit quality. The access Irai and C314, in the seedling stage, provided the best results. In the field, plants ungrafted obtained more accumulation total of dry matter, produticon rate of dry matter, relative growth rate, net assimilation rate, relative growth rate of leaf area, leaf area ratio and leaf weight. But, the specific leaf area was higher in grafted plants. Allied to this, the maximum plant height was 1.5 meters to 49 days after transplanting (DAT) in grafted plants and 42 DAT in ungrafted. The leaf dry matter (Wf) were increased. Regarding Wf, increased to 70 DAT in grafted plants (52.91 g m-2) and to 63 DAT in ungrafted (71.55 g m-2). Concomitantly, the number of leaves increased to 63 DAT. Regarding the dry matter of stem (Wc), the maximum was 6.56 g m-2 in grafted plants and 7.85 g m-2 in ungrafted, at 70 DAT. The dry matter of fruit (Wfr) started to compose the total dry matter from 42 DAT and was growing by the end of the cycle (70 DAT). For the grafted plant, Wfr maximum was 47.29 g m-2 and to ungrafted plants was 57.20 g m-2. The growth rate of leaf (Cf) increased until the end of the cycle with the Cf of 1.31 g m-2 d-1. Already, in ungrafted the Cf maximum was of 1.92 g m-2 d-1, at 49 DAT. The production rate of dry matter of stem (Cc) in the grafted watermelon was the maximum of 0.72 g m-2 d-1 (70 DAT), and grafted plants was 0.48 g m-2 d-1 (56 DAT). The growth rate maximum of fruit (Cf) was 3.66 g m-2 d-1 (70 DAT), in grafted plants. Already, the Cf in grafted plants was 2.97 g m-2d-1 (56 DAT). Grafted plants produced less than ungrafted, however, provided the best color of pulp and higher amount of phenols in the fruits did not differ in other variables when compared to ungrafted showing the potential of this material as a rootstock for hybrid mini watermelon Smile®.